Evaluation of transmission coefficients in nuclear processes - Oprea Cristiana; Oprea Alexandru Ioan (EPJ Web of Conferences)
Transmission coefficients for charged and neutral particles, without approximations for incoming and outgoing wave functions, were assessed using a quantum mechanical method based on reflection factor. Further, logarithmic derivative, using a rectangular potential in the internal region was computed. With a computer code developed by the authors, based on Hauser-Feshbach formalism, crosssections of fast neutron-induced reactions followed by the emission of charged particles were calculated. The code results show good agreement with experimental data when discrete states of residual nuclei are taken into account. By using integral form of penetrability coefficients, the current quantum-mechanical technique should be extended to continuous states of residual nuclei, including matching density levels represented by the Fermi-gas model.